Bio-stabilisation of granite residual soil using indigenous microorganisms - Ya Wang; Meiqi Li; Hao Peng; Jiaxin Kang; Chenlong Luo; Hong Guo; Yasheng Luo; Mingjiang Tao (PLoS ONE, 2025)
Granite residual soil exhibits inferior mechanical properties, which may lead to slope instability and embankment settlement. Microbial solidification technology offers an environmentally sustainable and highly effective approach for the improvement of such soils. To enhance the strength properties of granite residual soil in the Hanzhong region, three urease-producing Bacillus species, including Bacillus velezensis , Bacillus subtilis , and Bacillus tequilensis , are extracted from the soil in the same area, and solidification improvement experiments are conducted by changing the concentration of the cementing solution. The experimental results indicate that all three bacterial strains can substantially enhance the shear strength of soil. The optimal improvement effect for each strain is observed when the cementing solution concentration reaches 2 mol/L. Notably, Bacillus subtilis exhibits the greatest increase in internal friction angle, rising by 145.32% compared to the unimproved. In contrast, Bacillus tequilensis shows the highest improvement in cohesion, with a maximum increase of 316.19%. The solidification effect differed among different bacterial strains, with B. tequilensis and B. velezensis exhibiting better performance in high-concentration cementing solutions. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis reveal that the calcium carbonate precipitates in the soil solidified by these three types of bacteria can strongly bind to the soil particles, confirming the improvement effect at the microscopic level. This study provides an eco-friendly and cost-effective improvement method for the engineering application of granite residual soil, which plays an important role in improving the quality and decreasing the cost of artificial slope filling, roadbed filling, and foundation pit backfilling in areas with granite residual soil.